Athlete pose estimation by a global-local network - Hwang, J.; Park, S.; Kwak, N. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2017)
Analyzing joint movements of an athlete helps to improve the pose of the athlete. Human pose estimation (HPE) algorithms regress the locations of parts such as wrists, ankles and knees. In this paper, we propose a network that combines global and local information for HPE using a 2D image. Unlike previous works that have used global or local information separately, we use the combined information to enhance the performance of HPE. General information from a global network is used as an input to a local network to refine the location of a part using a variety of regions. The global network is based on ResNet-101 [6] and trained to regress a heatmap representing parts' locations. The output features from the global network are used as input features for the local network. The local network learns spatial information using position sensitive score maps [11]. Through the end-to-end learning, the global network is affected by the local information. We demonstrate that the proposed HPE method is efficient on the LSP and UCF sports datasets.